Understanding the anti-tumour immune response to radionuclide therapy using PSMA targeting radiopharmaceuticals in a prostate cancer model - Anderson, R (2021)
The ability of external beam radiation (EBRT) to modulate the tumour immune microenvironment is becoming increasingly well understood, leading to the development of combinatorial EBRT and immunotherapeutic combinations to improve patient responses. Despite this, there is very limited understanding of if, and how, the related modality of targeted radionuclide therapy (TRT) can interact with the immune system. Given its similarities with EBRT it seems likely that immune factors may play a role in the response to TRT. However, differences between the two radiotherapeutic modalities may result in some interesting differences that may be exploitable in combination therapies. As such, I sought to assess the impact of TRT on the tumour immune microenvironment, with the ultimate aim of identifying synergistic TRT and immunotherapy combinations.